Analysis of fatigue cracking of orthotropic steel decks using XFEM. (October 2022) - Zeng, Yong; Qu, Yu; Tan, Yujie; Jiang, Yuhang; Gu, Anbang
Highlights: A 3D XFEM model simulating experimental results of the longitudinal displacement of U-rib-to-diaphragm connections. DG-XFEM approach is used to analyze crack growth of the inside interior of the floor-beam. Contribution of the out-of-plane displacement to fatigue cracking can result in crack initiation and propagation prior. Abstract: The cutouts of diaphragms and the weld tips of the U-rib-to-diaphragm connections are the very complex structural details in orthotropic steel decks, and are accordingly highly vulnerable to fatigue cracking. The majority of fatigue cracks in these details appear as a result of the stress concentrations and initial weld defects. To determine the reason for the high probability of occurrence of fatigue cracks at these types of fatigue detail categories, a numerical model was established using the extended finite element method (XFEM) to analyze the cracking of diaphragm of an experimental 1:2 scaled deck segment model. This numerical analysis indicated that the cracks that appear at the diaphragm cutouts and near the weld toes of U-rib-to-diaphragm connections are induced by the relative horizontal displacement between the deck plate and diaphragm along the longitudinal axis of the bridge rather than by vertical deflection or moment due to live load. Additionally, stress concentrations play an important role in the initiation and propagation of cracks in these regions. The contribution of the out-of-plane displacement to fatigue cracking may be the most significant, and can frequently result in crack initiation and propagation prior to any cracking caused by vertical deflection or in-plane stresses. The XFEM approach is a useful numerical method for modelling the fatigue cracking of orthotropic steel decks.